2006
DOI: 10.1158/0008-5472.can-06-2442
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Receptor Coactivator-3 and Activator Protein-1 Coordinately Regulate the Transcription of Components of the Insulin-Like Growth Factor/AKT Signaling Pathway

Abstract: Steroid receptor coactivator (SRC)-3, also called amplified in breast cancer 1, is a member of the p160 nuclear receptor coactivator family involved in transcriptional regulation of target genes. SRC-3 is frequently amplified and/or overexpressed in hormone-sensitive and hormone-insensitive tumors. We reported previously that SRC-3 stimulated prostate cell growth in a hormone-independent manner through activation of AKT signaling pathway. However, the underlying mechanism remains undefined. Here, we exploited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(93 citation statements)
references
References 48 publications
(68 reference statements)
5
88
0
Order By: Relevance
“…AIB1 small interfering RNA (siRNA) oligonucleotides targeting different regions of AIB1 mRNA were synthesized by Qiagen. The AIB1 (1) siRNA target sequence is 5 ¶-AAAGA-CTCCTTAGGACCGCTT-3 ¶ (14), and the AIB1 (2) siRNA target sequence is 5 ¶-GGTGAATCGAGACGGAAAC-3 ¶ (12). The control siRNA used in the experiments is a scrambled sequence (5 ¶-AAUUCUCCGAACGUGUCACGUdTdT-3 ¶).…”
Section: Methodsmentioning
confidence: 99%
“…AIB1 small interfering RNA (siRNA) oligonucleotides targeting different regions of AIB1 mRNA were synthesized by Qiagen. The AIB1 (1) siRNA target sequence is 5 ¶-AAAGA-CTCCTTAGGACCGCTT-3 ¶ (14), and the AIB1 (2) siRNA target sequence is 5 ¶-GGTGAATCGAGACGGAAAC-3 ¶ (12). The control siRNA used in the experiments is a scrambled sequence (5 ¶-AAUUCUCCGAACGUGUCACGUdTdT-3 ¶).…”
Section: Methodsmentioning
confidence: 99%
“…These results substantiate the promoting effect of AIB1 on HCC cell cycle progression. Downregulation of AIB1 is frequently associated with inhibition of Akt signaling (Zhou et al, 2003;Oh et al, 2004;Yan et al, 2006), and inhibition of Akt signaling can lead to upregulation of the CDK inhibitor p21…”
Section: Downregulation Of Aib1 Suppresses Hcc Cell Proliferationmentioning
confidence: 99%
“…However, it has become increasingly apparent that the functions of SRC-3 are not limited to acting as a transcription coactivator of liganded nuclear receptors (Torres-Arzayus et al, 2004;Zhou et al, 2005;Yan et al, 2006b). For example, it was shown that prostate cancer cell proliferation requires SRC-3 for transitioning cells from the G 1 /G 0 phase to the S phase (Zhou et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…To understand the mechanism underlying the increased apoptotic activity in tumor cells deficient in SRC-3, we evaluated the expression of the proapoptotic gene, caspase-3 as well as the antiapoptotic gene, Bcl-2, in the thyroid of TRb PV/PV mice with or without SRC-3 by real-time reverse transcription-PCR ( Figure 4B) and western blot analysis ( Figure 4C). These two genes have been shown to be negatively or positively regulated by SRC-3 (Zhou et al, 2005;Yan et al, 2006b), respectively. Analysis by real-time RT-PCR indicates that the mRNA level of Bcl-2 was repressed by 31% in tumor cells deficient in SRC-3 (Figure 4Ba, compare bar 2 with 1).…”
Section: Deficiency Of Src-3 Increases Survival Of Trbmentioning
confidence: 99%